THE ROLE OF PROCESS RE-ENGINEERING IN RATIONALIZING COSTS AND STRENGTHENING THE COMPETITIVE POSITION OF INDUSTRIAL ENTITIES-APPLIED RESEARCH IN KARBALA CEMENT FACTORY (American Journal of Business Management, Economics and Banking, 2023)
In its theoretical framework, the research adopted the topic of process re-engineering and its related aspects, such as aspects of its concept, elements, importance, and stages of application, in addition to presenting the relationship between re-engineering and information technology, as well as the use of information technology in the field of industry. While the field frame of the study dealt with a presentation of the reality of cement factories in Iraq, and the extent of their need to bring about radical and comprehensive changes in all aspects of their work in order to keep pace with the developments and developments taking place in the Iraqi and international environments. The problem of the study focused on the ability of Iraqi bank administrations to understand and assimilate the process of re-engineering and its requirements as one of the most important strategies that must be adopted to meet the challenges and keep abreast of recent developments in the cement industry and modern information technology to rationalize its costs and enhance its competitive position.